2015
DOI: 10.1016/j.molcel.2015.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Human Hsp70 Disaggregase Reverses Parkinson’s-Linked α-Synuclein Amyloid Fibrils

Abstract: Summary Intracellular amyloid fibrils linked to neurodegenerative disease typically accumulate in an age-related manner, suggesting inherent cellular capacity for counteracting amyloid formation in early life. Metazoan molecular chaperones assist native folding and block polymerization of amyloidogenic proteins, preempting amyloid fibril formation. Chaperone capacity for amyloid disassembly, however, is unclear. Here, we show that a specific combination of human Hsp70 disaggregase-associated chaperone componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
408
4
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(446 citation statements)
references
References 30 publications
31
408
4
3
Order By: Relevance
“…Alternatively, the aggregation we observed could in part be due to a concomitant release of BiP and Grp170 as a consequence of simultaneous binding to these clients (model in Figure 7), which will be a less likely scenario for our peptides due to their much shorter length. In keeping with this possibility, a recent study with cytosolic orthologues of BiP and Grp170 found that Hsp110 (Apg2) promoted a coordinated dissociation of Hsp70 and a DnaJ protein from α-synuclein amyloid fibrils in vitro (Gao et al, 2015). Further studies are needed to resolve this point.…”
Section: Discussionmentioning
confidence: 95%
“…Alternatively, the aggregation we observed could in part be due to a concomitant release of BiP and Grp170 as a consequence of simultaneous binding to these clients (model in Figure 7), which will be a less likely scenario for our peptides due to their much shorter length. In keeping with this possibility, a recent study with cytosolic orthologues of BiP and Grp170 found that Hsp110 (Apg2) promoted a coordinated dissociation of Hsp70 and a DnaJ protein from α-synuclein amyloid fibrils in vitro (Gao et al, 2015). Further studies are needed to resolve this point.…”
Section: Discussionmentioning
confidence: 95%
“…There remains debate as to whether these proteins are sequestered as a consequence of aggregation, or if there is a physiological role for their presence. The recently-described ability of the Hsp70 chaperone complex to bind and facilitate disassembly of α-syn fibrils (35), provides support for an active role of these chaperones within aggregates. Previous studies have reported that αB-c and Hsp27 (as well as other sHsps) are present in Lewy bodies (36)(37)(38)(39)(40).…”
Section: Introductionmentioning
confidence: 92%
“…Pioneering work suggested that a mixture of Hsp70, Hsp40, and Hsp110 may disassemble amorphous aggregates but not amyloids (Nillegoda et al, 2015; Rampelt et al, 2012; Shorter, 2011). A provocative recent paper has further observed that a similar three chaperone system (Hsc70, DNAJC1, and Hsp110) cooperates to rapidly disaggregate α-synuclein fibrils into smaller seeds and monomer when present at the right stoichiometry (Gao et al, 2015). Moreover, another study has demonstrated that the serine protease HTRA1 solubilizes tau amyloids in an ATP-independent manner in vitro (Poepsel et al, 2015).…”
Section: Cellular Mechanisms Of Prion Propagationmentioning
confidence: 99%